Impact of the COVID-19 pandemic on emergency department utilization patterns in South Korea: A retrospective observational study. Issue 8 (25th February 2022) - Chang, Hyunglan; Kang, Min Woo; Paek, So Hyun
Abstract : Abstract: The purpose of analyzing changes in the use of emergency departments (EDs) was to better understand how to use ED resources efficiently during infectious disease outbreaks. Our study was a retrospective observational study. We analyzed the patterns of visits of adult and pediatric patients to separate EDs during 2020 coronavirus disease 2019 (COVID-19) outbreak to know the changes in the ED utilization. We collected the patient's demographics and time of visit, patients' acuity level at triage, cause of visit, transportation used, disposition, symptom to visit time, length of stay, and top 10 most common complaints. We compared pediatric and adult EDs before and after COVID-19. The total number of patients who visited the EDs was 197, 152 over 3 years. During the COVID-19 outbreak in 2020, the number of visits decreased significantly, especially the number of pediatric patients. The number of ED visits decreased in correlation with a surge in the number of confirmed COVID patients. The proportion of severe cases in pediatric emergency department (PED) visits increased, but there was no difference in adult emergency department. The number of hospitalized PED patients increased, and the number of hospitalized adult emergency department patients decreased. However, both types of ED patients increased in intensive care unit hospitalizations, proportion of deaths, and use of ambulances. The proportion of trauma patients in the PED increased significantly ( P  <  .001). The time from symptom onset to ED visit time was reduced for patients. The ED length of stay increased in adults, and decreased for pediatric patients. COVID-19 brought about many changes to ED utilization. A greater reduction in ED utilization occurred in pediatric patients compared to adult patients. Our study showed changes in the number and characteristics of patients visiting the ED during the COVID-19 period compared to 2018 and 2019.